Comparative Vegetation Analysis of some Plantation Ecosystems - Pande, P. K.; Bisht, A. P. S.; Sharma, S. C. (Indian Forester, 1988)
The present study deals with the comparative vegetation analysis of the four plantations of sal, teak, pine and eucalypts at New Forest, Dehra Dun. The higher density values and species richness in the plantations of pine, sal and teak were due to the stand maturity. The total basal cover (cm2 100 m-2) followed the order; Pine (5308.33)> sal (4002.21)> teak (2887.27)> eucalypts (1106.88), whereas IVI was the highest for eucalypts and sal (300) followed by teak (203.18) and pine (142.61) in their respective plantations. Comparatively, more diversity was observed for pine, while minimum for euculypts stand on both density and IVI basis. The distribution pattern of different tree species was contagious in all the plantations except pine, where it was random for most of the species. The highest values of concentration of dominance (on IVI basis) observed for sal and eucalypts, are attributed to the monospecific nature of their stands. In conclusion, it seems that different silvicultural operations like thinning, burning, weeding, etc. may create a possible route for the invasion of new species even during the premature age of the plantation.